Recycling of MBM ash wastes as CaO-P2O5 source in inorganic coating production - Yilmaz, Yasin Bozkurt; Cengiz, Tamer; Cicek, Bugra (SPRINGER, 2021)
Meat and bone meal (MBM) ash is a type of waste generated by the incineration of inorganics sourced from industrial livestock production. MBM ash contains 50-55 wt% calcium oxide (CaO) and 35-45 wt% phosphorus pentoxide (P2O5). It has the potential to be used as a raw material in the inorganic coating industry due to its chemical composition. In this study, the use of MBM ash as an environmentally friendly and cost-effective source of CaO and P2O5 is investigated in the production of inorganic coating raw material, i.e., frit on an industrial scale. Frits containing 3.5 wt% MBM ash are prepared. A commercially available frit is compared to the frit produced using MBM ash. The sintering behavior of fits is characterized by using heating microscope. An XRD analysis is carried out to verify the glassy structure of fits. The fits are applied on steel substrates using electrostatic powder method and subsequently fired at 830 degrees C for minutes. The surface properties, esthetic appearances, and chemical resistance of enamel coatings were comparatively analyzed. Analyses yield that MBM ash can be used as a source of CaO and P2O5 in inorganic coating raw material production and thus can be recycled for use in the economy.
Keywords: Enamel; Industrial sustainability; Raw materials; GLASS-CERAMICS; HYDROXYAPATITE; MEAT; Materials Science